2020
DOI: 10.33245/2310-9270-2020-157-1-96-103
|View full text |Cite
|
Sign up to set email alerts
|

Winter wheat varieties productivity of on elements of growing technology under the conditions of Southern Step of Ukraine

Abstract: Agrarian science has faced the problem of is the humanity provision with food, the major part of which is provided by grain crops. Winter wheat the most fully uses the existing bioclimatic potential of the Ukrainian regions. The highest productivity of this crop can be obtained with the use of modern adapted varieties with high genetic potential of productivity taking into account the soil-climatic conditions of the zone, improvement and development of highly effi cient, scientifi cally grounded systems of nut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
0
2
0
1
Order By: Relevance
“…All abovementioned factors force farmers in the south to adapt technologies for growing crops to both water scarcity and excessive moisture during certain vegetation periods. Application of mineral fertilizers and organo-mineral complexes with various pesticides is rationally combined, which not only allows increasing the productive potential of plants but also to reliably protects them from pathogen damage (Markovska et al, 2018;Markovska & Grechyshkina, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…All abovementioned factors force farmers in the south to adapt technologies for growing crops to both water scarcity and excessive moisture during certain vegetation periods. Application of mineral fertilizers and organo-mineral complexes with various pesticides is rationally combined, which not only allows increasing the productive potential of plants but also to reliably protects them from pathogen damage (Markovska et al, 2018;Markovska & Grechyshkina, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Research by Markovska and Hrechyshkina (2020) it was found the highest level of productivity was formed by plants of winter wheat of the Maria variety against the background of applying mineral fertilizers at a dose of N30P30 for pre-sowing cultivation using foliar top dressing with Organo-mineral fertilizer ROST (2.0 l/ha) at the beginning of the spring vegetation recovery and in the flag leaf phase. So, on average over the years of research, the grain yield in this variant was 4.96 tha -1 , the number of productive stems was 411 PCs/m 2 , number of grains in an ear was 27.6 PCs, the weight of 1000 grains were 51.5 g. Panfilova et al (2020) it was determined that the higher grain yield and slightly betterquality indicators differed grain of the studied winter wheat variety with the joint use of pre-sowing application of N30P30 and foliar fertilizing of winter wheat crops twice during the vegetation season by Escort-bio.…”
Section: Resultsmentioning
confidence: 99%
“…Winter wheat makes the fullest use of the existing bioclimatic potential of the regions of Ukraine. The highest productivity of this crop can be obtained if modern adapted variety with a high genetic potential of productivity are used, taking into account the soil and climatic conditions of the zone, improving and developing highly effective, scientifically based nutrition and protection systems against harmful organisms (Markovska and Hrechyshkina, 2020).…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 99%
“…One of the reasons for obtaining low yields of grain crops and losses during harves ting are abiotic factors. They can lead to annual 3-6-million-ton grain losses in Ukraine in unfavorable years (Lyubich, 2017;Bazalii et al, 2018;Markovska & Hrechishkina, 2020). The most harmful diseases of plants and ears affect the biochemical processes in the plant and grain.…”
Section: Introductionmentioning
confidence: 99%